The predictive value of neutrophil-lymphocyte ratio and mean platelet volume in patients with colorectal carcinoma (Annals of Medical Research, 2021)
Aim: This study aimed to investigate neutrophil-lymphocyte ratio (NLR) and mean platelet volume (MPV) for predicting colorectal cancer (CRC). Material and Methods: We investigated retrospectively patients who underwent colonoscopy. The study consisted of 75 patients with CRC and 91 study participants with normal colonoscopy as control group, and MPV and NLR were compared between groups. MPV and NLR were also investigated for tumor stage and metastasis. Results: Among the CRC patients the mean NLR value (3.09 vs 2.26) and PLT count (287080 vs 251857) were significantly higher, whereas the mean MPV (9.62 vs 10.68 fL) and hemoglobin level (11.62 vs 14.18 g/dl) were significantly lower in the CRC group. WBC count was not significantly different between the groups. Mean NLR in metastatic patients and non-metastatic patients were 3.56 and 2.73, respectively (p:0.01). Conclusion: We showed that high NLR and low MPV are associated with CRC. Elevated NLR is related with presence of CRC and it can be used for risk prediction. Although we found lower MPV levels, conflicting results about MPV in CRC prevents it from using as a marker in CRC.
Keywords: Colon polyp; colonoscopy; colorectal cancer; mean platelet volume; metastasis; neutrophil-lymphocyte ratio